Highly porous SnO2 nanosheet arrays sandwiched within TiO2 and CdS quantum dots for efficient photoelectrochemical water splitting - Wang, Zhiwei (2019)
A porous SnO2 nanosheets/TiO2/CdS quantum dots (SnO2 NSs/TiO2/CdS QDs) sandwich structure has been designed and fabricated as a “host-guest” photoanode for efficient solar water splitting applications. In this novel photoanode design, the highly porous SnO2 NSs serve as the host skeleton for efficient electron collection, while CdS QDs serve as efficient visible light absorbers. A thin interlayer of TiO2 is introduced for band alignment and reduction of charge recombination. Enhanced photoelectrochemical performance of the as fabricated photoanode is observed with introduction of the TiO2 interlayer. The optimized host-guest SnO2 NSs/TiO2/CdS QDs photoanode shows a photocurrent density as high as 4.7 mA cm−2 at 0 V versus Ag/AgCl, which is 7 times higher than that of the SnO2 NSs/TiO2 reference photoanode (0.7 mA cm−2). Furthermore, it also shows lower charge recombination rate compared to the SnO2 NSs/CdS QDs reference photoanode. Due to the high porosity and transparency of the as developed SnO2 NSs arrays host, it has great potential in various applications, such as solar energy conversion and energy storage.